Development of inclusive education theoretical model: Role of authentic leadership academic optimism and art-based pedagogies. Issue 6 (9th September 2019) - Srivastava, Anugamini Priya; Shree, Sonal
Abstract : Purpose: Inclusive organizations believe in integrating all toward synergistic outcomes. However, the extent to which inclusive education plays their role toward inclusive organizations requires more explorations. Therefore, the purpose of this paper is to provide a theoretical model exploring authentic leadership (AL) as a predictor of inclusive organization in an Indian school context. Design/methodology/approach: The paper theoretically develops a model to explore and establish inclusive classroom (IC) settings in emerging nations. Findings: The study further provides academic optimism (AO), a latent term comprising collective efficacy, faculty trust and academic emphasis as its dimensions to intervene the linkage between AL and IC. Since teaching pedagogies help teachers to express their real intentions, this study also posits art-based innovation pedagogy as a future-oriented art pedagogy to strengthen the effect of teachers' AO on IC. Originality/value: This study will benefit the practitioners and academicians to re-design their policies and practices in developing nation education system.